Assistance In The Quality Of MSME Marketing Through Social Media Marketing Innovation For Banana Chip Business Actors In Tanjung Sarana Village, Cihanjawar Village In 2023 - Fikri Irham Firdaus (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Marketing of UMKM in Cihanjawar village is still very lacking, due to limited knowledge about marketing using social media. The purpose of this service is to educate the public about marketing using social media facebook and whatsapp. The service method is carried out using the PAR (Participatory Action Research) method, which is a research method that is carried out definitively among community members. (Lorena Dara Putri Karsono, Fina Zahrotul Aniqoh, Chamidah Nor Aini, 2022). The steps taken by researchers in this service: first observing the potential of UMKM in Cihanjawar village, second innovating to make product packaging logos, third educating marketing using social media facebook and whatsapp. The result of this service is in the form of new product packaging using standing pouches along with packaging logos, and a wider market reach because it is marketed through social media. To find out an overview of how banana chip UMKM in Tanjung Sarana Village, Cihanjawar Village can take advantage of other social media by providing innovations in the products sold and expanding marketing by using Facebook, Whatsapp, for business benefits and introducing these products to the wider community in order to get a wider potential market share.